2021
DOI: 10.3389/fpsyt.2021.632660
|View full text |Cite
|
Sign up to set email alerts
|

Motivation-Enhancing Psychotherapy for Inpatients With Anorexia Nervosa (MANNA): A Randomized Controlled Pilot Study

Abstract: Patients with anorexia nervosa (AN) are frequently characterized by an unstable readiness to change and high ambivalence toward treatment. Enhancing readiness to behavioral change therefore plays an essential role for adherence to treatment especially for severely ill patients treated in inpatient settings. Therefore, a novel 10 week program for the individual psychotherapy sessions was designed using elements from motivational interviewing to be applied within the multidisciplinary inpatient treatment for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…After the first screening, there were 338 records eligible for the second screening. Twenty-two studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), five NRS [30][31][32][33][34], and one CBA [35]) were included as a result of the second screening and subject to data extraction. Studies excluded in the second screening can be found in the supplementary appendix (see Additional file 3).…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the first screening, there were 338 records eligible for the second screening. Twenty-two studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), five NRS [30][31][32][33][34], and one CBA [35]) were included as a result of the second screening and subject to data extraction. Studies excluded in the second screening can be found in the supplementary appendix (see Additional file 3).…”
Section: Search Resultsmentioning
confidence: 99%
“…Studies include between 20 [19] and 1531 [15] patients and are conducted in Australia [19,28], Denmark [14,34], France [31], GB [17,22], Germany [21,23,27,29,32,33], Italy [24], Netherlands [35], Norway [18], Switzerland [30], and the USA [15,16,20,25,26]. Five studies focus on patients with chronic pain [21,23,30,32,33], four studies on patients undergoing palliative care [16,19,20,26], and two studies on patients with neurological diseases (Parkinson's disease (PD) [24], multiple sclerosis [14]), cancer [27,31], or severe mental illness [34,35].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations